2014
DOI: 10.1007/s40257-014-0101-9
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Pemphigus Vulgaris and Pemphigus Foliaceus: A Systematic Review and Meta-Analysis

Abstract: Although some of the available therapeutic modalities for pemphigus are beneficial in terms of steroid-sparing, hastening response, or delaying relapse, none were found to increase the complete response rate compared with glucocorticoids alone, currently the mainstay of treatment. Multicenter randomized controlled trials and case control studies with uniform outcome measures are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
4

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 31 publications
0
25
0
4
Order By: Relevance
“…We also observed that patients with PV with mucocutaneous symptoms had the lowest EQ‐5D‐5L index scores, which highlights the importance of additional supportive treatments for patients with mucosal symptoms (e.g. topical corticosteroids, gels containing local anaesthetics and intralesional corticosteroid injections) …”
Section: Discussionmentioning
confidence: 58%
“…We also observed that patients with PV with mucocutaneous symptoms had the lowest EQ‐5D‐5L index scores, which highlights the importance of additional supportive treatments for patients with mucosal symptoms (e.g. topical corticosteroids, gels containing local anaesthetics and intralesional corticosteroid injections) …”
Section: Discussionmentioning
confidence: 58%
“…Published guidelines for pemphigus therapy mostly rely on expert consensus 129131 , given the paucity of randomized clinical trials with large sample sizes and rigorous randomization methods 132 .…”
Section: Managementmentioning
confidence: 99%
“…The superiority of one adjuvant has not been confirmed by trials. 59,60 PV and PF are the only conditions for which dermatological RCTs evaluating cyclophosphamide efficacy and safety have been performed.…”
Section: Pv and Pemphigus Foliaceus (Pf)mentioning
confidence: 99%